2019
DOI: 10.1016/j.jid.2018.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Culprit Drugs Induce Specific IL-36 Overexpression in Acute Generalized Exanthematous Pustulosis

Abstract: Acute generalized exanthematous pustulosis (AGEP) is a severe adverse cutaneous drug reaction. Although an involvement of drug-specific T cells has been reported, the physiopathology of AGEP and mechanism of neutrophilic skin inflammation remain incompletely understood. Recently, mutations in IL-36RN, the gene encoding the IL-36 receptor antagonist, have been reported to be more frequent in AGEP patients and pustular psoriasis. Here, we show that IL-36 cytokines, in particular IL-36g, are highly expressed in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 37 publications
0
34
0
1
Order By: Relevance
“…Similarly, doxycycline-inducible overexpression of wild-type KLF4 enhanced IL-36γ transcriptional activity, whereas a dominant-negative KLF4 mutant did not ( Figure 5B). This demon- exanthematous pustulosis (AGEP), and acrodermatitis continua Hallopeau (60,61). The data presented here provide substantial evidence that acneiform skin toxicity caused by EGFR/MEK inhibition should be added to the growing list of pustular skin diseases in which IL-36 likely plays a central pathogenic role.…”
Section: Klf4 Enhances Il-36γ Transcriptional Activity Upon Egfr/ Mekmentioning
confidence: 76%
“…Similarly, doxycycline-inducible overexpression of wild-type KLF4 enhanced IL-36γ transcriptional activity, whereas a dominant-negative KLF4 mutant did not ( Figure 5B). This demon- exanthematous pustulosis (AGEP), and acrodermatitis continua Hallopeau (60,61). The data presented here provide substantial evidence that acneiform skin toxicity caused by EGFR/MEK inhibition should be added to the growing list of pustular skin diseases in which IL-36 likely plays a central pathogenic role.…”
Section: Klf4 Enhances Il-36γ Transcriptional Activity Upon Egfr/ Mekmentioning
confidence: 76%
“…The recent studies about genetic predisposing identified mutation IL-36RN in AGEP patients [58]. These mutations lead to increase expression of various pro-inflammatory cytokines and chemokines such as IL-36 signaling, up-regulating IL-1, IL-6, CXCL 8/IL-8 production and neutrophil recruitment [54,59]. Etiology, pathology and treatments of SCARs have been extensively described as reviewed by other authors [60][61][62].…”
Section: Acute Generalized Exanthematous Pustulosis (Agep)mentioning
confidence: 99%
“…Recent studies suggested that PPP, generalized pustular psoriasis, and acute generalized exanthematous pustulosis are commonly characterized by unique molecular alterations associated with IL-36einduced neutrophilic inflammation (Arakawa et al, 2018;Johnston et al, 2017;Liang et al, 2017;Meier-Schiesser et al, 2019). IL-36 is a collective name for three members of the IL-1 superfamily: IL-36a, IL-36b, and IL-36g (Sims and Smith, 2010;Towne and Sims, 2012).…”
Section: Introductionmentioning
confidence: 99%